Possible role of the micronucleus assay in diagnostics and secondary prevention of cervix cancer: a minireview - Nersesyan, A.K. (Цитология и генетика, 2007)
Recent literature data are presented concerning micronuclei (MN) frequency in exfoliated cells of cervix cancer patients. These data strongly support a positive correlation between the MN level and malignization (changes from premalignant stage to cancer). It is suggested that the evaluation of frequency of MN in exfoliated cervical cells may be an additional criterion for establishing cervical cancer risk and the study of MN in cervix smears will increase the sensitivity and specificity of cytology which could impact in diagnostics and secondary prevention of cervical cancer.